2007
DOI: 10.1063/1.2794037
|View full text |Cite
|
Sign up to set email alerts
|

Phenol-water1⩽n⩽3 revisited: An ab initio study on the photophysics of these clusters at the level of coupled cluster response theory

Abstract: The S1(pi*<--pi) state surfaces of the phenol-water(1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…60 For the dihydrated complexes less information is available. In this case the first structure (Ph:W:W1) has been obtained before 63,[65][66][67] whereas the second (Ph:W:W2) is similar to the structure obtained by coupled cluster response theory CC2 model in ref. 65.…”
Section: 2supporting
confidence: 62%
See 1 more Smart Citation
“…60 For the dihydrated complexes less information is available. In this case the first structure (Ph:W:W1) has been obtained before 63,[65][66][67] whereas the second (Ph:W:W2) is similar to the structure obtained by coupled cluster response theory CC2 model in ref. 65.…”
Section: 2supporting
confidence: 62%
“…The hydrogen-bonded complexes of phenol with water have been intensely studied experimentally and theoretically, both the ground and the first S 1 excited state, with the aim of characterizing the structure, the rotation and vibration spectra and the fluorescence emission. 7,10,17,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Although the mono-hydrated Ph:W and W:Ph are of most interest here, in addition, two dihydrated complexes were also considered (Fig. 3).…”
Section: 2mentioning
confidence: 99%
“…Recently, theoretical work has elegantly explained the strange R2PI spectra of doubly-hydrated 2HN and phenol. 7,49 High resolution spectra of the sharp features observed in these experiments would provide the structure in S 0 and S 1 of these three-bodied clusters, as well as their associated electronic properties. Since these structures are expected to involve π hydrogen bonds, the energetics of which have recently have been quantified using the high resolution technique, 50 new information on weak and strong solvation effects could be measured.…”
Section: Discussionmentioning
confidence: 98%
“…[1] Hobza et al used ab initio methods to calculate several hydrogen-bonded structures and one hemibonded structure of the phenol-water cation radical. [1] Hobza et al used ab initio methods to calculate several hydrogen-bonded structures and one hemibonded structure of the phenol-water cation radical.…”
Section: Introductionmentioning
confidence: 99%
“…Phenol-water complexes have been investigated in a number of theoretical studies. [1] Hobza et al used ab initio methods to calculate several hydrogen-bonded structures and one hemibonded structure of the phenol-water cation radical. They found that the most stable structure has C s symmetry and features a linear hydrogen bond between the proton of the OH group of the phenol cation radical and the oxygen atom of water, with the water hydrogen atoms pointing away from the phenyl ring.…”
Section: Introductionmentioning
confidence: 99%